2014
DOI: 10.1186/s12870-014-0242-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of superoxide from Photosystem II in a rice (Oryza sativaL.) mutant lacking PsbS

Abstract: BackgroundPsbS is a 22-kDa Photosystem (PS) II protein involved in non-photochemical quenching (NPQ) of chlorophyll fluorescence. Rice (Oryza sativa L.) has two PsbS genes, PsbS1 and PsbS2. However, only inactivation of PsbS1, through a knockout (PsbS1-KO) or in RNAi transgenic plants, results in plants deficient in qE, the energy-dependent component of NPQ.ResultsIn studies presented here, under fluctuating high light, growth of young seedlings lacking PsbS is retarded, and PSII in detached leaves of the muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 106 publications
2
48
0
Order By: Relevance
“…This was partly supported by our results whereby the induction of NPQ was determined by the expression of both RVDE1 and PsbS1 under moderate light intensity (Figures 10A,B). Previous studies have indicated that the expression levels of genes coding PsbS and violaxanthin de-epoxidase were consistent with protein levels (Bugos and Yamamoto, 1996; Bugos et al, 1999; Ishida et al, 2011; Zulfugarov et al, 2014). However, under moderate light, the content of zeaxanthin and the relative expression of RVDE1 and PsbS1 of Chl-8 were significantly higher than Zhefu802 (Figures 9, 10).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This was partly supported by our results whereby the induction of NPQ was determined by the expression of both RVDE1 and PsbS1 under moderate light intensity (Figures 10A,B). Previous studies have indicated that the expression levels of genes coding PsbS and violaxanthin de-epoxidase were consistent with protein levels (Bugos and Yamamoto, 1996; Bugos et al, 1999; Ishida et al, 2011; Zulfugarov et al, 2014). However, under moderate light, the content of zeaxanthin and the relative expression of RVDE1 and PsbS1 of Chl-8 were significantly higher than Zhefu802 (Figures 9, 10).…”
Section: Discussionmentioning
confidence: 57%
“…Rice ( Oryza sativa L.) has two PsbS genes, PsbS1 and PsbS2 . However, only inactivation of PsbS1 results in plants deficient in qE (Zulfugarov et al, 2014). The relative expressions of all genes, with the exception of OSABA2 , in Chl-8 were significantly higher than those in Zhefu802 under moderate light (Figure 10).…”
Section: Resultsmentioning
confidence: 99%
“…The production of O 2 − can be detected using the dye NBT, forming dark blue insoluble formazan produced by the reaction of NBT. Histochemical staining for reactive oxidative species (ROS) production in leaf tissues has been used to identify sites of photo-oxidative stress responses in excess light [65], fluctuating light [66], enhanced ultraviolet-B radiation [67], and photoinhibitory illumination [68] as well as cadmium-treated stress [69] and water stress [70]. In-situ formation of H 2 O 2 can be visualized as reddish-brown coloration by forming perhydroxides precipitate or brown DAB-H 2 O 2 polymer [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that PsbS knock-out rice mutants produced more O 2 •– compared to WT under high light (Zulfugarov et al, 2014). The authors proposed that the lack of PsbS may cause shift in the midpoint redox potential of Q A /Q A •– redox couple to more negative value and thus enhance O 2 •– production by Q A •– .…”
Section: High Lightmentioning
confidence: 99%